Sexual health difficulties in a population-based sample of Croatian women aged 18-35 and the effects of the dual (career and motherhood) role - Štulhofer, Aleksandar (Array, 2011)
The prevalence of sexual health disturbances among women in Croatia is presently unknown. Although women under 40 years of age are often exposed to the most intense demands of the dual role (career and motherhood), they are frequently assumed to be at lower risk for sexual difficulties. Aim was to assess the prevalence of sexual disorders in a population-based study of women aged 18-35 and to explore the possible impact of the dual role on female sexual health. Methods. The study was carried out in April 2010 on a multi-stage probability sample (N=1, 000) of women aged 18-35 years. The response rate was 33 percent. Multivariate logistic regression was used to analyze the correlates of sexual difficulties, including the dual role. The prevalence of the four most common female sexual health difficulties (lack of desire, lubrication difficulties, inability to reach orgasm, and pain during intercourse) were measured using the indicators from the Global Study of Sexual Attitudes and Behaviors. Participants were asked if they experienced any of the four difficulties in the preceding year and were instructed to report only those that lasted for at least two months. Among coitally experienced women (N=870), 27.6% reported having a lack of desire, 23.6% pain during sexual intercourse, 23.1% inability to reach orgasm, and 18.5% difficulties with genital lubrication. All four disturbances were negatively associated with sexual satisfaction, but only the lack of sexual interest and inability to reach orgasm seemed to substantially decrease sexual well-being. In multivariate analyses, age, education, being in a steady relationship or married, and partner communication about sexuality were significant correlates of reported sexual difficulties. The dual role was not a significant predictor of sexual health disturbances. A substantial proportion of participants reported one or more sexual health difficulties. Contrary to expectations, women in the dual role were not at an increased risk of sexual health disturbances.